Antecedents of Intention to become a Social Entrepreneur: Studies in Undergraduate Students in Indonesia - Rosdiana Sijabat; Yerik Afrianto Singgalen (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2023)
This study empirically examines the antecedents of the intention to become a social entrepreneur by undergraduate students in Indonesia using the theory of planned behavior (TPB) framework. In TPB, the intention of a planned choice or desire is predicted to result from perceived attractiveness, subjective norms, self-efficacy, and personal attitudes. A total of 116 undergraduate students were recruited as respondents in this study, and primary data obtained from respondents were analyzed using structural equation modeling to test the four research hypotheses. This study revealed that the dimensions of perceived attractiveness, subjective norms, self-efficacy, and personal attitude of undergraduate students positively and significantly shaped students' intentions to become social entrepreneurs. Thus, the results of this study provide new understanding and knowledge about the antecedents to becoming a social entrepreneur.